2017
DOI: 10.1158/0008-5472.can-15-3231
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Detection of Cancer Biomarkers in Blood-Borne Extracellular Vesicles Using Nanodroplets and Focused Ultrasound

Abstract: The feasibility of personalized medicine approaches will be greatly improved by the development of noninvasive methods to interrogate tumor biology. Extracellular vesicles shed by solid tumors into the bloodstream have been under recent investigation as a source of tumor-derived biomarkers such as proteins and nucleic acids. We report here an approach using submicrometer perfluorobutane nanodroplets and focused ultrasound to enhance the release of extracellular vesicles from specific locations in tumors into t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Moreover, analyzing the gene expression profiles of microarray datasets on US‐treated cells, Yang et al (2017) showed that LIPUS enhanced EVs biogenesis and internalization. D'Souza et al also showed that US can be used to amplify and localize biomarkers in blood with a relatively simple and noninvasive strategy (D'Souza et al, 2009; Paproski, Jovel, Wong, Lewis, & Zemp, 2017). We observed an effective increased release of EVs upon LIPUS exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, analyzing the gene expression profiles of microarray datasets on US‐treated cells, Yang et al (2017) showed that LIPUS enhanced EVs biogenesis and internalization. D'Souza et al also showed that US can be used to amplify and localize biomarkers in blood with a relatively simple and noninvasive strategy (D'Souza et al, 2009; Paproski, Jovel, Wong, Lewis, & Zemp, 2017). We observed an effective increased release of EVs upon LIPUS exposure.…”
Section: Discussionmentioning
confidence: 99%
“…[19] The information conveyed by tumor-derived EVs may functionally influence recipient cells and foster their reprogramming, [20] thus contributing to the regulation of different stages of tumor progression. [21][22][23][24][25] Therefore, once released into the circulation, EVs and EV-associated molecules can be used as biomarkers in diagnosis, [26][27][28] prognosis, [29,30] and therapeutic follow-up of cancer patients. [31,32] The role of EVs in tumor progression has been addressed using mostly in vivo and conventional 2D in vitro models.…”
Section: Introductionmentioning
confidence: 99%
“…Building on this initial work, in vitro cell culture studies showed the feasibility of enhancing mRNA biomarker release from a breast cancer cell line using microbubble-enhanced ultrasound 11 , and the feasibility of releasing a combination of ovarian cancer biomarkers using ultrasound 12 . Two recent in vivo studies further demonstrated that ultrasound-mediated release of biomarkers into the bloodstream is a promising approach for detecting tumor biomarkers via blood sampling 13 , 14 . In one of the studies, pulsed HIFU with high acoustic pressures was used to induce histotripsy ( i.e.…”
Section: Introductionmentioning
confidence: 99%
“…, a technique for mechanical tissue fractionation) in a rat model of prostate cancer, and this enhanced release of cell-free tumor microRNA into the blood circulation 13 . In the other study, a chicken embryo tumor model was used to show the feasibility of amplifying the release of extracellular vesicles using high-intensity focused ultrasound (HIFU) in combination with phase-change nanodroplets which changed to microbubbles upon HIFU sonication 14 . Although promising, these preliminary findings cannot be readily extended to applications in the brain, given challenges inherent to the brain: first, delivery of acoustic energy to the brain is impeded by attenuation and distortion of acoustic waves by the skull; second, biomarker release from the brain is inherently limited by the presence of the BBB.…”
Section: Introductionmentioning
confidence: 99%